Eco-S.C.O.U.T - Muham Zaini, Muhammad Khairuddin; Amran, Aniq Syahmi; Ismail, Nur Izzati; Midin, Siti Aisyah; Kamarudin, Nur Syafiqah; Mohamed, Munirah (Universiti Teknologi MARA, Negeri Sembilan, 2025)
As the global demand for faster, safer, and greener delivery solutions grows, Eco-S.C.O.U.T (Eco-Friendly Smart Courier for Optimized Unmanned Transport) introduces a groundbreaking innovation in last-mile logistics. This fully autonomous delivery vehicle operates using solar, kinetic, and electric energy, enabling zero-emission functionality and significantly reducing its environmental impact. Eco-S.C.O.U.T is designed with sustainability, security, and reliability as top priorities. It features OTP-based parcel verification, real-time self-monitoring, and gyroscope-stabilized storage, ensuring that each package is delivered safely and accurately, even across challenging terrain and remote areas. The system addresses urban pollution and the inefficiencies of rural delivery networks while also serving as a strategic asset for developing eco-conscious infrastructure and smart cities. With its all-weather durability and intelligent automation, Eco-S.C.O.U.T can navigate complex environments without human intervention, helping to lower costs, reduce carbon footprints, and enhance service reliability. By combining advanced navigation, renewable energy integration, and a security-focused design, Eco-S.C.O.U.T represents a significant advancement in the evolution of sustainable logistics.